LOGICAL METHODS AND RULES OF REASONING IN DESCARTES AS TOOLS AGAINST BIAS IN JUDGEMENT - OGBUNKWU, Anacletus; Orji, Joseph Monday; CHUKWU, Donatus Oluwa (EBSU Journal of Social Sciences and Humanities, 2024)
Poverty of critical reasoning is one of the responsible factors for bias judgment and lots of related problems in the society. When reasoning is beclouded and hijacked by bias and prejudice then the inescapable effect include; discrimination, bigotry, chauvinism/feminism, violence, injustice, corruption in politics, religion and culture, etc. Thus the aim of this paper is to defend methods and rules of reasoning in Descartes as necessary tools against bias in judgment. In order to deal decisively to this aim as stated, expository and hermeneutical methods of research are applied to unveil Descartes rules of reasoning and to interpret these rules as necessary conditions for unbiased judgment. This study centers on the works of Descartes to expose his stand on foundations of knowledge in the cogito ego sum, 21 rules of reasoning which is summarized as; accept nothing as true that is not self-evident, divide problems into their simplest parts, solve problems by proceeding from simple to complex (logical consistency), recheck reasoning by enumeration. From the study, it is obvious that Descartes’ rules of reasoning are sufficient conditions for unbiased judgment. Therefore, the implication of this study is that a good application of these rules of reasoning in Descartes is preventive of bias in judgment.